Hubungan Motivasi Diri dan Pola Asuh Permisif dengan Prokrastinasi Akademik Mahasiswa Prodi Farmasi Universitas Sari Mutiara Indonesia di Medan - Tania Gultom; Hasanuddin Hasanuddin; Harun Sitompul (Mahesa Research Center, 2023)
The purpose of this study was to analyze the relationship between self-motivation and procrastination, permissive parenting with procrastination, self-motivation and permissive parenting with academic procrastination of Pharmacy Study Program students at Sari Mutiara Indonesia University in Medan.The type of research used in this research is quantitative research. The results of this study are as follows: (1) Self-motivation is negatively and significantly related to academic procrastination of Pharmacy Study Program students at Sari Mutiara Indonesia University in Medan with a t count > t table (-2.067 > 1.65309) and a significance value of t is smaller than 0.05 (0.040 <0.05); (2) Permissive parenting has a positive and significant relationship with academic procrastination of semester students of Pharmacy Study Program at Sari Mutiara Indonesia University in Medan with a t count > t table (9.571 > 1.65309) and a significance value of t is less than 0.05 (0.000 < 0, 05); (3) Self-motivation and permissive parenting have a joint effect on the variable of academic procrastination in students of the Pharmacy Study Program at Sari Mutiara Indonesia University in Medan with a F count > F table (50.867 > 3.04) and a significance value of t is less than 0.05 (0.000 <0.05).